HEXIM1 Peptide Exhibits Antimicrobial Activity Against Antibiotic Resistant Bacteria Through Guidance of Cell Penetrating Peptide - Ho, Pooi Leng; Ong, Han Kee; Teo, Jeanette; Ow, Dave Siak-Wei; Chao, Sheng-Hao (Frontiers in Microbiology, 2019)
The emergence of antibiotic resistant bacteria is one of the biggest threats to human health worldwide. In 2017, World Health Organization listed the world’s most dangerous antibiotic-resistant bacteria or “superbugs”, such as carbapenem-resistant Pseudomonas aeruginosa and Escherichia coli, indicating the highest priority needs for new antibiotics. The possibility that such infectious diseases may soon be untreatable, due to decreased antibiotic efficacy, creates an urgent need for novel and alternative antimicrobials. Antimicrobial peptides are naturally occurring small molecules found in the innate immunity of mammals, plants and bacteria, and are potentially therapeutic candidates against drug-resistant bacteria. In this study, we examine the antimicrobial activities of the cytotoxic peptides derived from the basic region (BR) of the human hexamethylene bisacetamide-inducible protein 1 (HEXIM1). We found that, when fused with a cell penetrating peptide, the HEXIM1 BR peptide and its derivative, BR-RRR12, exhibited inhibitory activities against selected “superbugs”. Negligible effects on the viability of human keratinocyte cell line were observed when the bactericidal dosages of HEXIM1 BR peptides were used. Different killing kinetics were observed between the membrane permeabilizing antimicrobial peptides and HEXIM1 BR peptides, suggesting that a different antimicrobial mechanism might be utilized by the HEXIM1 BR peptides. Using an in vitro translation system based on E. coli lysates, we found that HEXIM1 BR peptides blocked bacterial translation. Taken together, we identify the HEXIM1 BR peptide as a novel antimicrobial peptide with potent inhibitory activity against antibiotic-resistant “superbugs”.